Does hand position affect orienting when no action is required? An electrophysiological study - Reed, Catherine L.; Garza, John P.; Bush, William S.; Parikh, Natasha; Nagar, Niti; Vecera, Shaun P. (Frontiers in Neuroscience, 2023)
Previous research has shown that attention can be biased to targets appearing near the hand that require action responses, arguing that attention to the hand facilitates upcoming action. It is unclear whether attention orients to non-targets near the hand not requiring responses. Using encephalography/event-related potentials (EEG/ERP), this study investigated whether hand position affected visual orienting to non-targets under conditions that manipulated the distribution of attention. We modified an attention paradigm in which stimuli were presented briefly and rapidly on either side of fixation; participants responded to infrequent targets (15%) but not standard non-targets and either a hand or a block was placed next to one stimulus location. In Experiment 1, attention was distributed across left and right stimulus locations to determine whether P1 or N1 ERP amplitudes to non-target standards were differentially influenced by hand location. In Experiment 2, attention was narrowed to only one stimulus location to determine whether attentional focus affected orienting to non-target locations near the hand. When attention was distributed across both stimulus locations, the hand increased overall N1 amplitudes relative to the block but not selectively to stimuli appearing near the hand. However, when attention was focused on one location, amplitudes were affected by the location of attentional focus and the stimulus, but not by hand or block location. Thus, hand position appears to contribute only a non-location-specific input to standards during visual orienting, but only in cases when attention is distributed across stimulus locations.